(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Agriculture has been the prime source of livelihood for a majority of India’s population. Land and peasant, therefore, have held a central position in its repository of fictional narratives in regional languages. The exploitation of the peasants in both colonial and postcolonial India is evident through these narratives. Both the advent and the end of British rule in India brought a drastic change in land relations and repressive and exploitative schemes for the peasants. What gave the ‘tax– collector mediators’ ownership of the land, bringing exploitative Zamindari system in the colonial regime through legislation like Permanent Settlement Act 1793, became difficult to eradicate on the ground level in the multi– layered agrarian structure in postcolonial India. The Land Reform project of Independent India proceeded with four significant steps: abolition of Zamindari, tenancy reforms, fixing land ceilings and consolidation of landholdings under the chairmanship of the Gandhian Economist J.C. Kumarappa, brought minuscule change for small peasants. Covering a period of around six decades with reference to select short stories in Hindi Literature, the paper attempts to study the representation of the peasant, the land and the exploitative power mechanisms affecting the relationship between the two. The relationship between the exploiter and the exploited is further complicated and complemented by the stringent hierarchal caste system. Nevertheless, the paper will study caste relations as a subtheme. Finally, through Narratology, I shall critically analyse the changes in the narration and characterisation in the chosen time span led by various Hindi Literary movements.